Anti-Biofouling Polymers with Special Surface Wettability for Biomedical Applications - He, Zhoukun; Yang, Xiaochen; Wang, Na; Mu, Linpeng; Pan, Jinyuan; Lan, Xiaorong; Li, Hongmei; Deng, Fei (Frontiers in Bioengineering and Biotechnology, 2021)
The use of anti-biofouling polymers has widespread potential for counteracting marine, medical, and industrial biofouling. The anti-biofouling action is usually related to the degree of surface wettability. This review is focusing on anti-biofouling polymers with special surface wettability, and it will provide a new perspective to promote the development of anti-biofouling polymers for biomedical applications. Firstly, current anti-biofouling strategies are discussed followed by a comprehensive review of anti-biofouling polymers with specific types of surface wettability, including superhydrophilicity, hydrophilicity, and hydrophobicity. We then summarize the applications of anti-biofouling polymers with specific surface wettability in typical biomedical fields both in vivo and in vitro, such as cardiology, ophthalmology, and nephrology. Finally, the challenges and directions of the development of anti-biofouling polymers with special surface wettability are discussed. It is helpful for future researchers to choose suitable anti-biofouling polymers with special surface wettability for specific biomedical applications.